Sustainability communication in marketing: a literature review - Luiza Dazzi Braga; Matheus Grage Tardin; Marcelo Gattermann Perin; Patricia Boaventura (RAUSP Management Journal)
Purpose – This study aims to explore the foundations and current research streams of sustainability communication (SC) within the marketing field through a comprehensive analysis of the existing literature. Furthermore, it identifies promising areas, gaps, and guides for future contributions in SC literature. Design/methodology/approach – This study relies on a sample of 103 articles published in high-ranked marketing journals. Through co-citation and qualitative thematic analyses, it examines a network over the foundations and central themes in current literature. Findings – In the marketing field, the foundations of SC rest on institutional and stakeholder theories, corporate social responsibility (CSR) communication and its effectiveness, green advertising, ethical consumerism and marketing strategies, and social marketing for sustainable consumption. Additionally, the analysis reveals four core current themes: reporting sustainability, sustainability advertising, consumer reactions, and promoting pro-sustainable behaviour. Research limitations/implications – This paper defines the foundations and boundaries of SC in marketing based on a comprehensive evaluation of existing research. By doing so, it offers a valuable reference for future research, enabling scholars to understand better the past and current state of SC in marketing and to identify areas for further investigation. Practical implications – Businesses and marketers can use the findings to develop more effective SC strategies and to focus on the main topics that require their attention. Social implications – This research is of societal importance because it deepens our understanding of SC in marketing. It illuminates uncharted territory and helps decision-makers across sectors create a more sustainable future. In essence, this research enriches society by promoting sustainability awareness and guiding the development of practices that emphasize the value of SC. Originality/value – This study advances previous literature reviews on SC in the marketing field by providing a roadmap for researchers to delve deeper and contribute to the field of SC in marketing, advancing our understanding of the importance of organizations effectively communicating their sustainability strategies to stakeholders.